Antibacterial activity and compositional analysis of Acer truncatum bunge leaf extract against Staphylococcus aureus - F Liao; J He (Veterinární Medicína)
Staphylococcus aureus is a zoonotic pathogen that can cause various diseases in both humans and animals. This experiment evaluates the antibacterial activity of extracts from Acer truncatum leaves against S. aureus, including the minimum inhibitory concentration (MIC), growth curve, and cell membrane integrity assessment, alongside the identification of the extract components by LC-MS. Results demonstrated that the MIC of the n-butanol extract from the ethanol extract of Acer truncatum leaves against S. aureus was 3.125 mg/ml, with a minimum bactericidal concentration (MBC) of 6.25 mg/ml. Over 16 h, the extracts at concentrations of 0.25 MIC, 0.5 MIC, and 1 MIC effectively inhibited S. aureus growth. The fluorescence staining revealed that the extracts at different concentrations compromised the structural integrity of the cell membrane. The LC-MS analysis identified the principal constituents of the extract as betaine (27.189%), 3,4-dihydroxymandelic acid (16.112%), quercitrin (14.768%), chlorogenic acid (8.778%) and neochlorogenic acid (4.452%). The study indicated that Acer truncatum leaf extract has good potential for application in natural antibacterial drugs.